Financial Crime and Punishment: A Meta-Analysis - Laure de Batz; Evzen Kocenda (Charles University in Prague, Institute of Economic Studies (IES), 2020)
We examine how the publication of intentional financial crimes committed by listed firms is interpreted by financial markets, using a systematic and quantitative review of existing empirical studies. Specifically, we conduct a meta-regression analysis and investigate the extent and nature of the impact that the publication of financial misconducts exerts on stock returns. We survey 111 studies, published between 1978 and 2020, with a total of 439 estimates from event studies. Our key finding is that the average abnormal returns calculated from this empirical literature are affected by a negative publication selection bias. Still, after controlling for this bias, our meta-analysis indicates that publications of financial crimes are followed by statistically significant negative abnormal returns, which suggests the existence of an informational effect. Finally, the MRA results demonstrate that crimes committed in common law countries, alleged crimes, and accounting crimes carry particularly weighty information for market participants. The results call for more transparency on side of enforcers along enforcement procedures, to foster timely and proportionate market reactions and support efficient markets.
Keywords: C83; G14; G18; K42; N24; 330; Meta-Analysis; Event study; Financial Misconduct; Fraud; Financial Markets; Information and Market Efficiency; Returns; Listed Companies